(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Abstract This study deals with the problem of chemical and physical pollution of water and how to treat it by analyzing the data obtained statistically, and build statistical models linking the concentrations of chemical pollutants in the Tigris River water by estimating the correlation between the percentage of chloride contaminant and some other chemical pollutants, which provides us quick references. The validity of the Tigris River water is determined for its daily use in Maysan governorate. The method used to select the best estimated regression equation using (Backward Elimination) method , to select only those elements of significant effect in order to construct tables of statistical indicators that can be consulted quickly to indicate the suitability of water for daily use. In order to construct a model, we can explain the concentration of chloride ion in the Tigris River. The beneficiary of the estimated equations used to estimate the concentration of chloride ions in water, and to note the risks of the use of this water, the study found significant differences between the average chlorides according to the time of data recording, and exceeded the chloride contaminant International and Iraqi rates are allowed and water is contaminated.